2022
DOI: 10.1093/cid/ciac219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vaccination and Pediatric Age on Delta Variant Household Transmission

Abstract: Background The impact of SARS-CoV-2 vaccination status and paediatric age on transmission of the Delta variant is key to preventing COVID-19 spread. In Singapore, quarantine of all close-contacts, and quarantine-entry and exit PCR testing, enabled evaluation of these factors. Methods This retrospective cohort study included all household close-contacts between March 1, 2021 and August 31, 2021. Logistic regression using gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…During these waves there has been speculation that children have become more susceptible to SARS-CoV-2 infection and more infectious once they contract the virus. For example, during the Delta wave in Singapore children (aged 0-11 years) were significantly more likely to transmit and acquire SARS-CoV-2 in a household compared to young adults (18-29 years) [5]. Similarly, during the Omicron wave in the USA the secondary attack rates (SAR) were consistently high across household contact and index age groups, including those aged 0-4 years old [6].…”
Section: Introductionmentioning
confidence: 99%
“…During these waves there has been speculation that children have become more susceptible to SARS-CoV-2 infection and more infectious once they contract the virus. For example, during the Delta wave in Singapore children (aged 0-11 years) were significantly more likely to transmit and acquire SARS-CoV-2 in a household compared to young adults (18-29 years) [5]. Similarly, during the Omicron wave in the USA the secondary attack rates (SAR) were consistently high across household contact and index age groups, including those aged 0-4 years old [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (4/15) summarised the vaccination status of the entire study sample, which ranged from an undefined proportion of partially vaccinated individuals to 70% fully vaccinated, without analysing it at the individual level for adults and children and adolescents. 17,56-58…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (4/15) summarised the vaccination status of the entire study sample, which ranged from an undefined proportion of partially vaccinated individuals to 70% fully vaccinated, without analysing it at the individual level for adults and children and adolescents. 17,[56][57][58] Six studies evaluated data from alpha variant outbreaks in daycare centres and compared the risk of infection between children and adults. 14,18,[50][51][52][53] They generally showed a lower attack rate for infection with the alpha variant ranging from 0% to 27% for young children (mostly ≤6 years old) than for adults (0%-71%).…”
Section: Review Question 1: Symptoms and Severity Of Disease Among Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…Oon Tek Ng et al ( 20 ) reported that among the Delta variant-exposed household contacts, the male index cases (adjusted odds ratio (aOR), 0.86; 95% CI, 0.49–1.49) had no significant association with the reduced risk of SARS-CoV-2 acquisition. Meanwhile, another study ( 21 ) by Oon Tek Ng et al showed that male index cases had a significant association with an increased risk of SARS-CoV-2 acquisition (aOR, 1.23; 95% CI, 1.04–1.46) among the Delta variant-exposed household contacts. More studies are needed regarding the association between the gender of the index cases and household SAR.…”
Section: Discussionmentioning
confidence: 99%